Unlocking the Healing Potential: A Comprehensive Review of Ecology and Biology of Medical‐Grade Honey in Wound Management and Tissue Regeneration - Parmis Barazesh; Helia Hajihassani; Fatemeh Motalebi; Seyedeh Mobina Hosseini Neiresi; Romina Hajihassani; Ahmad Reza Mehrabian (Health Science Reports)
ABSTRACT Background and Aims Honey has long been studied for its healing abilities in wound care. This narrative review examines its properties and their impact on wound healing, particularly its ability to accelerate wound closure and promote tissue regeneration. The review focuses on how honey's botanical origins affect its medical properties and wound‐healing capabilities. Finally, clinical studies on honey's effectiveness in wound healing were reviewed compared to traditional treatments. Methods Relevant keywords were searched in databases, yielding 1250 documents. After excluding nonrelevant sources, 450 documents were refined, and 167 articles were selected based on thematic alignment and originality. Data extraction focused on study design, intervention details, and outcomes, with quality assessed using standardized criteria. The study adhered to CONSORT and SANRA guidelines to ensure methodological rigor and reporting transparency. Results Honey‐based medical products have demonstrated significant antibacterial, anti‐inflammatory, and tissue‐regenerative properties, making them highly effective in improving wound healing outcomes, particularly in chronic and burn wounds. These products have also been shown to reduce infection rates and hospital stays. While some studies have reported positive outcomes in accelerating the healing process, others have found no significant difference compared to conventional treatments. Conclusion Medical‐grade honey (MGH) holds potential for wound care due to its versatility, though variations in its composition present challenges. Further research is needed to optimize its clinical use. The effectiveness of MGH in wound healing remains debated, with mixed results from trials. Genetic modification of bees to enhance MGH's properties could make it more competitive against conventional treatments. Honey‐based medications could reduce costs, improve energy efficiency, and have minimal side effects. Rigorous research is necessary to determine optimal use and fully unlock MGH's potential, which could revolutionize wound management globally.